Effect of furosemide treatment on the central and peripheral pressor responses to cholinergic and adrenergic agonists, angiotensin II, hypertonic solution and vasopressin - Colombari, Débora Simões de Almeida [UNESP]; Colombari, Eduardo [UNESP]; Saad, Wilson Abrão [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP]; Renzi, Antonio [UNESP]; Luca Junior, Laurival Antonio de [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 1992)
The present study was performed to investigate the effect of treatment with furosemide on the pressor response induced by intracerebroventricular (i.c.v.) injections of cholinergic (carbachol) and adrenergic (norepinephrine) agonists, angiotensin II (ANGII) and hypertonic saline (HS, 2 M NaCl). The changes induced by furosemide treatment on the pressor response to intravenous (i.v.) norepinephrine, ANGII and arginine vasopressin (AVP) were also studied. Rats with a stainless-steel cannula implanted into the lateral ventricle (LV) were used. Two injections of furosemide (30 mg/kg b.wt. each) were performed 12 and 1 h before the experiments. Treatment with furosemide reduced the pressor response induced by carbachol, norepinephrine and ANGII i.c.v., but no change was observed in the pressor response to i.c.v. 2 M NaCl. The pressor response to i.v. ANGII and norepinephrine, but not AVP, was also reduced after treatment with furosemide. These results show that the treatment with furosemide impairs the pressor responses induced by central or peripheral administration of adrenergic agonist or ANGII, as well as those induced by central cholinergic activation. The results suggest that the treatment with furosemide impairs central and peripheral pressor responses mediated by sympathetic activation and ANGII, but not those produced by AVP. © 1992.
Keywords: Adrenergic drug; Angiotensin II; Diuretic; Furosemide; Hypertension; Vasopressin; Angiotensin; Argipressin; Carbachol; Furosemide; Noradrenalin; Animal experiment; Blood pressure; Catecholaminergic system; Cholinergic system; Controlled study; Drug sensitivity; Intracerebroventricular drug administration; Intramuscular drug administration; Intravenous drug administration; Male; Nonhuman; Priority journal; Rat; Animal; Argipressin; Blood Pressure; Carbachol; Injections, Intravenous; Injections, Intraventricular; Male; Norepinephrine; Rats; Saline Solution, Hypertonic; Support, Non-U.S. Gov't; Vasoconstriction